Pesan Nonverbal pada Ekspresi Cinta dalam Film "Midnight" - Nababan, Joan Natasya; Delliana, Santi (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2024)
An expression of love is an image of an emotional state or feeling of affection that indicates the way a person expresses love for an action or behavior. Expressions of love that occur in life can be represented by movie. The purpose of this research is to find out about nonverbal messages in the expression of love in Midnight using the paradigm of Constructivism. The research was conducted using a qualitative approach with the semiotic method of Charles Sanders Peirce who had Sign, Object, and Interpretant. The results of this research is showing expressions of love through facial expressions, gestures, body language, touch, an appearance that shows the expression of an mother-child love, and vice versa, accompanied by intimate closeness to interactions in mother-child relationships which make it a close relationship, looking at each other, protect each other in a dangerous situation by giving a physical touch like hugging.